Implementing Competitive Bidding in the Medicare Program: An Expressway to Solvency - Rohini Chakravarthy MD, MBA; Gail R. Wilensky PhD; Brian J. Miller MD, MBA, MPH (SAGE Publishing, 2022)
The Medicare program faces increasing budgetary pressures, with recent estimates suggesting that the Medicare Hospital Insurance Trust will be insolvent as soon as 2028. Simultaneously, the Medicare Advantage (MA) program, a managed competition model, continues to grow its market penetration as beneficiaries increasingly choose private plans over traditional fee for service (FFS) Medicare. With the relative cost of the 2 forms of Medicare a subject of debate, policy experts have proposed a variety of policy options to address the program's budgetary pressures and place it on a firmer fiscal footing. This paper explores the implementation of one of these proposals in greater detail: fully transitioning the entire Medicare program to a competitive bidding model in order to reduce overall program costs and improve price competition. Current MA plan bidding methodology is explored, followed by a description of prior proposed competitive bidding models. Implementation challenges are addressed, along with specific policy considerations to protect beneficiaries who wish to remain in FFS Medicare.